Factors Pressuring Worker's Personal Wellbeing at Media Workplace Environment - Rosidayu Sabran; Nur Kareelawati Abd. Karim (European Publisher, 2024)
Work and the environment of today's human life often cause stress. Media convergence has changed the media industries, which in turn, acquires new technological systems, organisational structure and patterns of production processes. Changes in the way we work in today's digital technology era continue to create work stress. One of the industries associated with extreme work stress is the creative media industry. A working culture based on business profit orientation had always been about productivity in producing creative ideas and creative products. Unfortunately, there may not be many employers who are particular about ensuring workers' mental and emotional health as part of their efforts to inculcate employee productivity. Therefore, this paper seeks to identify factors affecting the wellbeing of media workers in Malaysia, the extent to which these factors shape their wellbeing, and how these media workers manage such challenges. The qualitative research approach was executed through an online interview to collect data among media workers of several electronic and print media. Data were analysed using thematic analysis approach. The findings had identified factors influencing the wellbeing of media workforce and strategies to manage pressures within media work environment. Factors relating to production management, workplace policy, organisational leadership and technology transformation constraint are the challenges faced by Malaysian media practitioners affecting their wellbeing.